Sleepwalker [large type] - Robards, Karen (Wheeler Publishing, 2012)
"Micayla Lange isn't afraid of the clinking she hears downstairs in her uncle Nicco's McMansion. She's a cop after all. In Jason Davis's line of work, getting caught red-handed by a hot police officer in the murder of a city councilman. Or realizing the security cameras got a good look at him and the cop, which means they're both as good as dead. Mick and Jason team up on a race for their lives. As enemies close in, Mick is torn between her duty to the force and the passion engulfing her and her unlikely partner in crime"-- Cover verso.